The Changing Nature of the Just War Tradition: How Our Changing Environment Ought to Change the Foundations of Just War Theory. (12th September 2017) - Hedahl, Marcus; Clark, Scott; Beggins, Michael
Abstract : It is becoming ever more apparent how quickly and dramatically our environment is changing. That changing environment must, in turn, change the way we think about just war theory. When examining jus ad bellum, jus in bello, jus post bellum, and a novel set of considerations referred to as jus para bellum, it becomes apparent that there exists an urgent need for changes not only to the content of just war principles, but also to the principles themselves.